The contribution of traditional healers' clinics to public health care system in Addis Ababa, Ethiopia: a cross-sectional study - Birhan Wubet; Giday Mirutse; Teklehaymanot Tilahun (BMC, 2011)
Abstract Background Ethiopian people have been using traditional medicine since time immemorial with 80% of its population dependent on traditional medicines. However, the documentation of traditional healers' clinics contribution to modern public health system in cosmopolitan cities is scanty. Studies conducted so far are limited and focused on the perceptions and practices of modern and traditional health practitioners about traditional medicine. Thus, a cross sectional study was conducted from February to May 2010 to assess the contribution of traditional healers' clinics to public health care system in Addis Ababa. Materials and methods Ten traditional healers who were willing to participate in the study and 306 patients who were visiting these traditional healers' clinics were interviewed using two types of semi-structured questionnaires. Data were summarized using percentages, tables and bar chart. Results The diseases mostly treated by traditional healers were wound, inflammation, herpes zoster, hemorrhoids, fracture, paralysis, back-pain, liver diseases, cancer and eczema. This study showed that traditional healers' clinics considerably contribute to public health care in Addis Ababa. Fifty two percent of patients reported that traditional healers' clinics were their first choice when they faced health problems. The reasons for visiting these clinics were 175 (57.2%) efficacy, 109 (35.6%) dissatisfaction with modern medicine, 10 (3.3%) dissatisfaction with modern medicine and efficacy, 6 (2.0%) cost and 6 (2.0%) dissatisfaction and cost. Females (55.2%), young age (20-40 years, 65.0%), never married (56.9%), orthodox (73.9%), Amhara (52.3%), educational status above grade 12 (34.6%) and government employees (29.4%) were frequent visitors. Healers reported that there was no form of cooperation with modern health professionals. The reasons were lack of motivation to collaborate and communicate with modern health service workers. Family based apprenticeship was the sources of knowledge for majority of the healers. Conclusions The study conducted showed that for the majority of patients interviewed traditional healers' clinics were one of the options to solve their health problems that indicated the considerable contribution of these clinics to the public health care system in Addis Ababa. Nevertheless, in this study the contribution of traditional healers' clinics to the public health system would have been better shown if individuals who are not users of the traditional healers' clinics were included in the interview. However, the study might be useful as a base line data for future evaluation of the significance of traditional healers' clinics for public health system and the services rendered in these clinics.